MyT brewer. part a - Mendonca, Valerie; Aggarwal, Ansita (London : Indian Institute of Management, Ahmedabad, 2024)
Amit Kasliwal founded MyT in 2014 subsequent to completion of his PGPX course at the Indian Institute of Management, Ahmedabad. He envisioned a machine that brewed and dispensed fresh tea and tried a number of prototypes that addressed different issues/challenges. In September 2015, he moved to Bengaluru along with his co-founder Harvinder Rajput and iterated a variety of prototypes with a designer. Kasliwal and his team were able to develop a machine that brewed and dispensed tea in December 2016. Around the same time, Kasliwal ran out of funds. Although the latest prototype dispensed freshly brewed tea, there were still a number of improvements to be implemented. Kasliwal was faced with a dilemma whether he should go ahead and enter the market or continue building a better prototype.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Tea machinery -- Technical innovations -- Case studies; Selling -- Tea -- Case studies